Characterization of Bacterial Community Structure in a Drinking Water Distribution System during an Occurrence of Red Water - Li, Dong (American Society for Microbiology (ASM), 2010)
The role of bacteria in the occasional emergence of red water, which has been documented worldwide, has yet to be determined. To better understand the mechanisms that drive occurrences of red water, the bacterial community composition and the relative abundance of several functional bacterial groups in a water distribution system of Beijing during a large-scale red water event were determined using several molecular methods. Individual clone libraries of the 16S rRNA gene were constructed for three red water samples and one sample of normal water. Beta-, Alpha-, and Gammaproteobacteria comprised the major bacterial communities in both red water and normal water samples, in agreement with previous reports. A high percentage of red water clones (25.2 to 57.1%) were affiliated with or closely related to a diverse array of iron-oxidizing bacteria, including the neutrophilic microaerobic genera Gallionella and Sideroxydans, the acidophilic species Acidothiobacillus ferrooxidans, and the anaerobic denitrifying Thermomonas bacteria. The genus Gallionella comprised 18.7 to 28.6% of all clones in the three red water libraries. Quantitative real-time PCR analysis showed that the 16S rRNA gene copy concentration of Gallionella spp. was between (4.1 ± 0.9) × 10(7) (mean ± standard deviation) and (1.6 ± 0.3) × 10(8) per liter in red water, accounting for 13.1% ± 2.9% to 17.2% ± 3.6% of the total Bacteria spp. in these samples. By comparison, the percentages of Gallionella spp. in the normal water samples were 0.1% or lower (below the limit of detection), suggesting an important role of Gallionella spp. in the formation of red water.